2007
DOI: 10.1007/s10143-007-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Rebleeding of ruptured cerebral aneurysms during three-dimensional computed tomographic angiography: report of two cases and literature review

Abstract: Although three-dimensional computed tomographic angiography (3D-CTA) is less complicated and time-consuming than conventional cerebral angiography (CCA) and represents a reliable alternative for evaluating cerebral aneurysms, some patients experience aneurysmal rerupture during 3D-CTA. Two women, 79 and 71 years old, who presented with severe subarachnoid hemorrhage (SAH) underwent 3D-CTA within 3 h after SAH onset. Their images clearly indicated extravasation from their aneurysms. Neither patient recovered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…This discrepancy may be due to the difference of emergency medical delivery system. Consistent with previous reports [3][4][5][6]10,11,15) , we experienced rebleeding during angiogram (4 cases) and anesthesia (5 cases). Thus, more careful attention will be necessary while performing these procedures.…”
Section: Discussionsupporting
confidence: 81%
“…This discrepancy may be due to the difference of emergency medical delivery system. Consistent with previous reports [3][4][5][6]10,11,15) , we experienced rebleeding during angiogram (4 cases) and anesthesia (5 cases). Thus, more careful attention will be necessary while performing these procedures.…”
Section: Discussionsupporting
confidence: 81%
“…20 Thus, even slight enhancement in the subarachnoid space can be observed more easily on a thick-slab maximum-intensity-projection image than on a volume-rendered image (Fig 3), because volume-rendering is an operator-dependent technique. Although string-shaped extravasation in SAH often mimics vascular structures, [20][21][22][23] multiphase CT imaging is superior to routine CTA, differentiating between extravasation and vascular structures, including aneurysms, because extravasated contrast medium is not washed out in the delayed phase (Fig 4).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] In addition, active bleeding from an aneurysm was recently visualized with 4D time-resolved CT angiography. 5 Use of multiphase dynamic enhancement can increase the time window for hemodynamic observation, and the evolution of bleeding Extravasation had a vessel-like shape at the interhemispheric cistern (A, arrow), and spreading contrast extravasation was observed in the left ventricle (B, arrow).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of CTA for the detection of cerebral aneurysm is reportedly equivalent to that of angiography, and this modality provides more information for performing surgical procedures, and can be performed non-invasively within a short period of time, making it useful for the diagnosis of cerebral aneurysm [13,14]. Nakatsuka et al performed CTA on 28 patients with subarachnoid hemorrhage and reported a rebleeding rate of 17.9% [15], while Hashiguchi et al reported rebleeding in 2 of 61 patients (3.3%) [16]. As rebleeding also occurred in 4 patients (6.7%) in our own series, occurrence during CTA is far from infrequent.…”
Section: Case 5 (Figure 5)mentioning
confidence: 99%
“…Table 2 shows a summary of reported cases [16][17][18][19][20][21] Rebleeding was more common in patients with severe subarachnoid hemorrhage and tended to be more frequent in those who underwent CTA within 3 h of initial bleeding, but no consistent findings were seen with respect to aneurysm location. Outcomes were poor for patients who experienced rebleeding.…”
Section: Case 5 (Figure 5)mentioning
confidence: 99%